2019
DOI: 10.29228/turkishstudies.36938
|View full text |Cite
|
Sign up to set email alerts
|

Portföy Yatirimlari İle CDS Arasindaki̇ İli̇şki̇: Türki̇ye Örneği̇

Abstract: This article was checked by iThenticate.  Bu çalışma 04-06 Nisan 2019 tarihinde İzmir (Çeşme)'de gerçekleştirilen 3. Uluslararası Uygulamalı Sosyal Bilimler Kongresinde özet olarak sunulan bildirinin tam metin olarak düzenlenmiş halidir.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…In order to confirm the Granger causality test, the variables were subjected to time-varying causality test and again no causality relationship was detected throughout the periods analysed. When the results of the study are compared with other studies in the literature, it is similar to the results of Öztürk et al (2018), while it differs from the results of Fei, Fuertes and Kalotychou (2017), Koy and Karaca (2018), Kahıloğulları (2018), Yıldırım and Sakızcı (2019), Sevil and Ünkaracalar (2020), İlter and Gök (2021), Şenol et al (2023). It is thought that the difference between the results of other studies in the literature and the principle is due to the date range used and different analysis methods.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…In order to confirm the Granger causality test, the variables were subjected to time-varying causality test and again no causality relationship was detected throughout the periods analysed. When the results of the study are compared with other studies in the literature, it is similar to the results of Öztürk et al (2018), while it differs from the results of Fei, Fuertes and Kalotychou (2017), Koy and Karaca (2018), Kahıloğulları (2018), Yıldırım and Sakızcı (2019), Sevil and Ünkaracalar (2020), İlter and Gök (2021), Şenol et al (2023). It is thought that the difference between the results of other studies in the literature and the principle is due to the date range used and different analysis methods.…”
Section: Discussionsupporting
confidence: 81%
“…In the study, a unidirectional causality was found between CDSs and foreign equity investments, that is, from CDS premiums to foreign equity investments. Fei, Fuertes and Kalotychou (2017), Koy and Karaca (2018), Kahıloğulları (2018), Yıldırım and Sakızcı (2019), Sevil and Ünkaracalar (2020), İlter and Gök (2021), Şenol et al (2023), there is a relationship between CDSs and foreign portfolio investments, either cointegration or causality, and in the estimates of the degree of the relationship in all studies except İlter and Gök (2021), there is a negative relationship between CDSs and foreign portfolio investments. Öztürk et al (2018) examined the relationship between foreign direct investments and economic growth in Türkiye with the help of time series analyses for the period between 1974 and 2016.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Ancak çoğu ülke toplam sermaye gereksinimlerini iç kaynaklarla karşılayamadığından yabancı yatırımlara yönelmektedir. Hem gelişmiş hem de gelişmekte olan ülkeler, yatırımları teşvik etmek, ekonomik büyümeyi artırmak, üretimdeki (Seyidoğlu, 2017;UNCTAD, 1999;Yıldırım ve Sakızcı, 2019).…”
Section: Introductionunclassified